NEXUS Gains Talk 10: Nexus Tools to Support Solarization of Agriculture in Asia and Africa - Verma, Shilp; Xie, Hua (CGIAR System Organization, 2023)
This seminar introduces a solar irrigation pump sizing tool developed for and adopted in India, with potential for expansion to other countries in South Asia, as well as tools developed for Sub-Saharan Africa.